Pengaruh Model Learning Together (belajar bersama) dalam Memahami Wacana Tulis di Kelas XI SMA RK Delimurni Delitua - Sri Mardiana (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2021)
This study aims to describe students' ability to understand written discourse by using two variables, to find out whether there is a significant effect on the ability to understand written discourse using Learning Together in class XI SMA RK Deli Pure Delitua. The instrument is in the form of multiple choice with 4 answer choices, namely a, b, c, and d with 20 questions each. The data analysis technique used to see the relationship between the independent variables (Learning Together learning model) and the dependent variable (understanding written discourse) was used product moment correlation analysis and to test the hypothesis used the t test formula. From the research that has been done, it was found that the increase in the ability to understand written discourse that was treated with the Learning Together learning model had an average of 75.97 and those who were treated using the NHT learning model had an average of 64.44. The normality test for the experimental class is Lcount = 0.1278 (Lcount = 0.1278 < Ltable = 0.1476, while the control class Lcount = 0.1340 (Lcount = 0.1340 < Ltable = 0.1476. While the hypothesis test shows that ( Ha) is accepted so that there is an influence using the Learning Together learning model in understanding written discourse in the class of SMA RK Deliputih Delitua.